The Use of TikTok Application for Learning Speaking Skills: A Simple Teaching Research - Heryani, Wiwin; ., Senowarsito; Nur'Aini, Siti (KnE Social Sciences, 2024)
Speaking skill is commonly reflected to be the most crucial skill to attain. Many media platforms can be used to learn speaking skills independently such as using the TikTok application. This study is intended to know and describe the students’ preferences and learning experiences regarding the use of TikTok application as a supplementary tool for enhancing speaking skills. The study was carried out with 36 students of State School 1 of Tahunan grade XI science program in the academic year 2022/2023 divided into 18 couples. The researcher used a purposive sampling technique in determining the participants. This study used a descriptive method with a qualitative approach and used questionnaires to collect data. The learning material used was a TikTok homepage or account with videos available online. The researchers asked the students to watch the videos within a two weeks time frame. The study found that the students watching the shared videos through TikTok to regularly learn in classes can help improve speaking ability. Learning speaking skills on TikTok is psychologically fun and stress-free. TikTok is relatively easy to access, varied video and interesting content, easy to understand, and the students can learn from native speakers for free. Besides, TikTok can effectively improve the students’ speaking ability. Keywords: TikTok application, a TikTok homepage or account, speaking skill